FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI LANSIA DI DESA TANJUNG ANOM WILAYAH KERJA PUSKESMAS PANCUR BATU KABUPATEN - Endang Junita Sinaga; Hotmarina Lumba Gaol (STIKes Santa Elisabeth Medan, 2017)
Elderly is the life stage of the individual, this phase of this life must be passed by every individual, health conditions at this stage is largely determined by the quality and quantity of nutrient intake. In addition to nutritional intake such as energy and protein intake, physical activity can also contribute to the state of nutritional status of the elderly. Pancur Batu Puskesmas Goals : Deli Serdang has posyandu elderly in every rural area working area of puskesmas. One of them is an elderly service posyandu unit in Tanjung Anom Village. This study aims to see the factors that affect the nutritional status of elderly in posyandu elderly village tanjum anom. Method : The research design used is cross sectional study approach. This study has a sample of 38 people, by way of taking purposive sampling. The tools used in data collection are questionnaire and Food Frequency Quetionnaire (FFQ). Results : The results showed that the majority of women (68.5%), unfulfilled protein intake 55.3%, 50% unmet energy intake, and physical activity 73.7%. The results showed that protein intake and physical activity factors were associated with nutritional status of the elderly, as evidenced by p = 0,004 and 0,003. Conclusion: The conclusion of the study was that low intake of protein and energy led to nutritional status of the elderly. It is recommended that family members living with the elderly can balance the intake of protein and energy that is tailored to the type of physical activity of the elderly everyday.